2007
DOI: 10.1016/j.joen.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

KAI-1 Protein Expression in Odontogenic Cysts

Abstract: The KAI-1 tumor suppressor gene is widely distributed in normal tissues and its down-regulation may be correlated with the invasive phenotype and metastases in several different epithelial tumors. The aim of the present study was an evaluation of KAI-1 expression in radicular cysts (RC), follicular cysts (FC), orthokeratinized keratocysts (OOKC), and parakeratinized keratocysts (POKC). Eighty-five odontogenic cysts, 28 RC, 22 FC, and 35 OKC (16 OOKC, 19 POKC) were selected. All the POKC were negative and only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Prominent palisaded and hyperchromatic nuclei in the basal cell layer are not seen in OOC. Many studies have also found different histochemical and immunohistochemical features in OOC from OKC, including significant differences in keratin profiles in the cyst lining epithelium [10], in collagen fibers, fibronectin, or numbers of myofibroblasts in the cyst wall [11][12][13][14], in expression of podoplanin [15], Ki-67, p63 [3], TGF-a, P53 [16], bcl-2 [17], KAI-1 [18], cell proliferating marker IPO-38 [19], calretinin [20], EMA, CEA, and involucrin [21]. These findings lead to the current concept that OOC is a different pathological entity from OKC.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent palisaded and hyperchromatic nuclei in the basal cell layer are not seen in OOC. Many studies have also found different histochemical and immunohistochemical features in OOC from OKC, including significant differences in keratin profiles in the cyst lining epithelium [10], in collagen fibers, fibronectin, or numbers of myofibroblasts in the cyst wall [11][12][13][14], in expression of podoplanin [15], Ki-67, p63 [3], TGF-a, P53 [16], bcl-2 [17], KAI-1 [18], cell proliferating marker IPO-38 [19], calretinin [20], EMA, CEA, and involucrin [21]. These findings lead to the current concept that OOC is a different pathological entity from OKC.…”
Section: Discussionmentioning
confidence: 99%
“…[26,27] One of the newest markers studied in odontogenic cysts is KAI-1. [28] KAI-1 has been detected in normal human tissues and is a regulator of cell behaviour. The expression of KAI-1 has been seen to decrease in cancer cell lines with high propensity for metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Not much has been reported about the KAI-1 expression in odontogenic cysts, and there has been a paucity of studies in the literature regarding the expression of KAI-1 in the odontogenic apparatus. Extensive search revealed one study conducted by G Iezzi et al [28] in which the authors found a positive KAI-1 expression in radicular and dentigerous cysts but very little expression in OKCs amongst which none of the parakeratinised OKCs showed positivity and only 4 out of 16 orthokeratinised OKCs revealed KAI-1 could, thus, be related to the factors peculiar to extensive cystic lesions, including their locally aggressive behaviour, high mitotic activity of their cells and their tendency to recur, although the rate of recurrence might depend on the method and adequacy of their treatment. This p53 reactivity, thus, indicates the possible role it plays in the high intrinsic growth potential and biological aggressiveness of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This method of counting the KAI-1 positive cells was according to Iezzi et al . [ 15 ] The surface layer constituted flattened or polygonal cells consisting of one to five layers, localized just beneath the surface of the lining epithelium. The suprabasal/intermediate layer was composed of relatively large round cells between the basal and the surface layers.…”
Section: Methodsmentioning
confidence: 99%